Alfredo Pareja: ensayista y crítico - Ortega Caicedo, Alicia (2008)
The author reviews the essays of Alfredo Pareja on issues of colonial art, culture and literature. It recounts the evolution of his notion of the artistic since 1933, when Pareja distances himself from the previous generation and the Arielism in force at that time, by making the defense of socialist realism his; later though, connecting these judgments in other essays. His critical point of view, gene rally speaking, does not defend the originality or the form of a text in and of itself, but the value of the content; humanism begins to be the guiding thread in his fiction and iIIuminator of his sense of esthetics. On the other hand, he feels the need to redefine the local in its contact with the universal, recognizing the love of contemporane ousness in his generation; his defense of the mestizo is shown in his reflectíons on the Latín American Baroque Movement. Fínally, it is interesting that Pareja compares two great moments in Ecuadorian Art: the colonial painting and sculpture of the Quito School, and the aesthetic notions of hís generation.